Thermal extraction of water ice from the lunar surface - A 3D numerical model. (15th November 2020) - Brisset, Julie; Miletich, Thomas; Metzger, Philip
Abstract: We have used a three-dimensional thermal and gas diffusion model to study the heated extraction of water ice from lunar regolith. Both surface heating and the insertion of heated drills were investigated for various heating power levels and expected soil ice fractions. Our calculations rely on the use of the Crank-Nicolson finite difference method for the diffusion equations. We find that the extraction of water vapor from lunar regolith requires high levels of heating power in the investigated configurations. Any heating below about 1000 ​W per m 2 or per heated drill produces negligible amounts of vapor. We also find that extraction efficiencies are highly dependent on the heating configuration, as well as the initial ice fraction present in the regolith. In addition, we find that, depending on the heating configuration, significant amounts of water escape the heated volume and are lost through refreeze in colder regions. We conclude that water extraction through heating will be a power-hungry process if not optimized through additional controls (e.g. volume confinement by heated walls). In addition, the choice of a heating configuration for optimal extraction efficiency depends on the ice content of the soil. Therefore, detailed prospecting will be essential to the design of future ISRU activities on the Moon. Graphical abstract: Image 1 Highlights: Water extraction from Lunar polar regions is a crucial technique to understand. We use 3D simulations of thermal extraction of water ice from the Lunar soil. Heating from the surface and through inserted drills is investigated. Water vapor recovery in various configurations is presented.